Analisis Atas Pelaporan SPT PPH Pasal 21 Klien Pada Perusahaan Konsultan XYZ - Davina, Nazwa; Fatimah, Sukma; Lenap, Indria Puspitasari; Putri, Sarina Adila (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to analyze the reporting of Income Tax (PPh) Article 21 Notification Letters (SPT) of clients at XYZ consulting company. This research is descriptive with a qualitative approach. Three informants participated in the study namely, tax staff, marketing managers, and accounting staff at consulting firm XYZ. The results of the study indicate that the reporting mechanism of XYZ consulting company is in accordance with tax reporting procedures. The main obstacles faced are delays in receiving data from clients and technical difficulties in accessing the DJP Online system. Mitigation efforts are carried out through intensive communication with clients and technical assistance. Despite facing various technical and administrative obstacles, tax reporting for both companies and individuals is always carried out on time, in accordance with the deadlines set by the DJP. This is an important commitment maintained by the consultant team to maintain client compliance and trust.